2009
DOI: 10.1002/em.20455
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene polymorphisms are associated with the risk of developing adenomyosis

Abstract: Vascular endothelial growth factor (VEGF), a major mediator of angiogenesis and vascular permeability, may play a key role in the development of adenomyosis. The aim of this study was to investigate whether these four VEGF polymorphisms (-2578C/A, -1154G/A, -460C/T, and +936C/T) were associated with the risk of adenomyosis development. Genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay in 174 adenomyosis patients and 199 frequency-matched control wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The study of Kang et al the -2578A or -1154A allele of VEGF gene significantly decreased the risk of adenomyosis and was considered potentially protective factor for adenomyosis development [30].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Kang et al the -2578A or -1154A allele of VEGF gene significantly decreased the risk of adenomyosis and was considered potentially protective factor for adenomyosis development [30].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (32) reported that abnormal secretion of IL-6 and IL-8 from endometrial stromal cells may have a role in the formation of ectopic islands in adenomyosis. Furthermore, the role of EGF, VEGF and TGF-β implicated in inflammation, angiogenesis and the pathophysiology of endometriosis has been well established (36)(37)(38). Cell invasion is a vital hallmark of tumor formation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion criteria, 14 studies were included (Hsieh et al, 2004;Bhanoori et al, 2005;Kim et al, 2005;Ikuhashi et al, 2007;Gentilini et al, 2008;Kim et al, 2008;Zhao et al, 2008;Cosin et al, 2009;Kang et al, 2009;Liu et al, 2009a,b;Attar et al, 2010;Lamp et al, 2010;Altinkaya et al, 2011). The flow chart of study selection is shown in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%